Hadis tentang Menuntut Ilmu sebagai Landasan Filosofis Pendidikan Islam - Wawan, Wawan Darmawan; Mirza , Iskandar (Jurnal Penelitian Tarbawi: Pendidikan Islam dan Isu-Isu Sosial, 2026)
Seeking knowledge is a fundamental principle in Islamic teachings with direct implications for the conception and practice of Islamic education. The hadith of the Prophet Muhammad (peace be upon him) explicitly states the obligation to seek knowledge for every Muslim, indicating that education in Islam is not merely a social need but a theological duty. This article aims to analyze the hadiths concerning the pursuit of knowledge and position them as the philosophical foundation of Islamic education, viewed from ontological, epistemological, and axiological aspects. The method used is library research with a descriptive-analytical approach to hadith sources and Islamic education philosophy literature. The study's results show that the hadith on seeking knowledge forms an integral Islamic education paradigm, oriented towards the development of human intellectual, spiritual, and moral potential. Thus, the hadith on seeking knowledge functions as a philosophical foundation in formulating the holistic and transformative goals, methods, and values of Islamic education. Keywords: hadith, seeking knowledge, philosophy of islamic education, islamic religious education.